ANALISIS EVALUASI PEMBELAJARAN PPKN DALAM PENGUATAN NILAI KARAKTER SISWA SEKOLAH DASAR - Syifa, Anzilnii Asy; Pasaribu, Debora Keiko; Sitompul, Arika Angelia; Laurencia, Rachell Maretta; Manjani, Nurhudayah (Jurnal Merah Putih Sekolah Dasar, 2025)
This study aims to analyze the results of learning evaluation in Pancasila and Citizenship Education (PPKn) to assess the strengthening of character values among elementary school students. Learning evaluation serves not only to measure cognitive achievement but also to assess affective and psychomotor aspects related to character development. This research employed a descriptive qualitative approach with a case study method conducted at SDN 060791 Medan Area. Data were collected through classroom observations, in-depth interviews with the PPKn teacher, and documentation analysis of assessment rubrics, teacher journals, and students’ assignments. The findings indicate that PPKn learning evaluation can identify the reinforcement of character values such as responsibility, discipline, cooperation, honesty, and patriotism. Evaluation instruments used include attitude rubrics, project-based assignments, behavioral observations, and student self-reflections. However, several challenges were identified, including limited instructional time, administrative workload, and the lack of systematically structured affective assessment instruments. Therefore, PPKn learning evaluation needs to be designed in a systematic and continuous manner to function as an effective reflective tool for strengthening character education in elementary schools.